Desempenho a partir das capacidades especializadas de marketing e orientação empreendedora no comércio varejista de vestuário - Matte, Juliana (My University, 2018)
Due to the growing concern of companies to achieve superior performance in a complex competitive environment, the role of marketing capabilities is becoming a differential. This is because retailers with strong marketing capabilities tend to offer products and services that better meet customers' needs compared to their competitors. As a result, efforts to anticipate demand to position new product / service offerings generally result in superior performance. This proactivity, assumption of risk and innovation that make the company anticipate the market are characteristics of the entrepreneurial orientation, which propitiates the competitiveness in the market, achieving a superior performance. Therefore, this research had as main objective to examine the relationship between the specialized marketing capabilities (product, price, channel, communication), the entrepreneurial orientation and the firm performance of the retail clothing trade of Caxias do Sul - RS, from a theoretical model that represents the positive impact that each specialized marketing capability and entrepreneurial orientation have on the firm performance. The applied research method consisted of a quantitative approach, consisting of a survey with 200 stores of the clothing retail trade of Caxias do Sul - RS. For analysis, the Structural Equation Modeling technique was used. The results indicated that product, channel and marketing communication capabilities positively influence the firm performance, as well as the entrepreneurial orientation, explaining 48% of the firm performance. The price capacity did not confirm the hypothesis that it has a positive relation with firm performance. As for the moderators, only companies with more than six years or more of activity moderate the relationship between marketing communication capabilities and firm performance, demonstrating the concern and importance that these companies give to communication actions, unlike young companies. Among the variables that most represented the model are the entrepreneurial orientation and the channel capacity, indicating that companies that constantly seek novelties, concerned with understanding and serving their customers, create, invent new business, relationship, product and / or positioning themselves ahead of their competitors. Thus, they create barriers to imitation (initial capacity base), since they are in constant rearrangements (characteristic of innovation belonging to the entrepreneurial orientation). Therefore, finding new ways to strengthen and deepen the relationship with its customers, creates a lasting bond and enables the company to surprise them, sustaining itself in the market.
Devido à crescente preocupação das empresas em alcançar desempenho superior em um ambiente competitivo complexo, o papel das capacidades de marketing está se tornando um diferencial. Isso ocorre porque os varejistas com fortes capacidades de marketing tendem a oferecer produtos e serviços que atendam melhor às necessidades dos clientes em comparação com seus concorrentes. Consequentemente, os esforços em antecipar a demanda para posicionar novas ofertas de produtos/serviços geralmente resultam em um desempenho superior. Essa proatividade, assunção de risco e inovação que fazem com que a empresa se antecipe ao mercado são características da orientação empreendedora, que propicia a competitividade no mercado, alcançando um desempenho superior. Portanto, esta pesquisa teve como principal objetivo examinar a relação entre as capacidades especializadas de marketing (produto, preço, canal, comunicação), a orientação empreendedora e o desempenho das empresas do comércio varejista de vestuário de Caxias do Sul – RS, a partir de um modelo teórico que representa o impacto positivo que cada capacidade especializada de marketing e orientação empreendedora causam no desempenho da empresa. O método de pesquisa aplicado consistiu em uma abordagem quantitativa, constituída de uma survey com 200 lojas do comércio varejista de vestuário de Caxias do Sul – RS. Para análise, foi utilizada a técnica de Modelagem de Equações Estruturais. Os resultados indicaram que as capacidades de produto, canal e comunicação de marketing influenciam positivamente o desempenho da empresa, assim como a orientação empreendedora, explicando 48% do desempenho da empresa. A capacidade de preço não confirmou a hipótese de que possui relação positiva com o desempenho. Quanto aos moderadores, apenas as empresas com mais de seis anos ou mais de atividade moderam a relação entre as capacidades de comunicação de marketing e o desempenho, demonstrando a preocupação e importância que essas empresas dão às ações de comunicação, diferentemente das empresas jovens. Entre as variáveis que mais representaram o modelo estão a orientação empreendedora e a capacidade de canal, indicando que empresas que buscam constantemente novidades, preocupadas em entender e atender seus clientes, criam, inventam novas formas de negócio, de relação, de produto e/ou serviços, se posicionando à frente de seus concorrentes. Com isso, propiciam a criação de barreiras à imitação (base inicial das capacidades), pois estão em constantes rearranjos (característica da inovação pertencente à orientação empreendedora). Portanto, encontrar novas formas de estreitar e aprofundar o relacionamento com seus clientes, cria um laço duradouro e possibilita que a empresa possa surpreendê-los, se sustentando no mercado.
Keywords: Marketing; Empreendedorismo; Comércio varejista; Desempenho; Entrepreneurship; Retail trade; Performance